Diabets- The Global Challenge of HealthCare - Kekelashvili, Khatuna; Kvantcakhadze, Rusudan (Caucasus Journal of Health Sciences and Public Health, 2020)
Diabetes Mellitus is one of the most important healthcare problems. According to its spread, we can say, that the pandemic of diabetes is on the earth. Diabetes exceeds only private medicine, medical aid or medical measures and gains public importance. Naturally, it is impossible to defeat diabetes or eliminate the problem. It is likely to be inevitable even for its spread, but it is possible to reduce the growth rate, which will only enable the joint actions of all areas of society to be considered in the context of diabetes as a social problem, and only medical and healthcare uniform approaches are possible.